Metabolic disturbances, histopathological analysis, and virus detection in chicken following infection with fowl adenovirus serotype 8b - Norfitriah Mohamed Sohaimi,; Muhammad Aidil Haikal Mohd Dzilan,; Mohd Hair Bejo,; Azalea Hani Othman, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Fowl adenovirus (FAdV) serotype 8b is a causative agent of inclusion body hepatitis (IBH) in chickens with serious economic impact due to huge mortality in commercial farms. To date, analysis of metabolic disturbances caused by FAdV serotype 8b infection in chicken is scanty although FAdV is highly pathogenic in specific pathogen free (SPF) chicken. It is important to highlight the effect of the FAdV infection for better control strategy against the disease. The objective of the study is to determine the metabolic parameters, virus detection, and histopathological analysis of chickens following infection with FAdV serotype 8b. Fifteen-day-old SPF chicks were divided into two groups namely, the infected group and the control group. All chicks in the infected group were inoculated with 1 mL FAdV isolate, UPM1901, via oral route at day 7 of age, while all chicks in the control remained uninoculated. At 0, 3, and 7 days post-inoculation (dpi), blood and serums were collected for clinical biochemistry analysis followed by histological examination and virus detection using polymerase chain reaction (PCR). Marked anemia with an elevation of aspartate-aminotransferase (AST) and gamma-glutamyl transferase (GGT) levels in infected chickens at 3 and 7 dpi with low creatine kinase levels than control group were recorded due to liver damage caused by FAdV infection. Swollen, hemorrhage, and necrosis of the liver were observed in chicken from the infected group at 3 and 7 dpi with evidence of basophilic intranuclear inclusion bodies in degenerated hepatocytes. Liver, kidney, and lymphoid organs were positive for FAdV at 3 and 7 dpi in the infected group. It was concluded that FAdV serotype 8b isolate UPM1901 induces metabolic disturbances and histopathological lesions with detectable viral nucleic acid in the liver and lymphoid organs which necessitates effective therapeutic strategy for liver protection and a better immune response against IBH disease.